Interaction based on method for spam detection in online social networks - Kan CHEN; Liang CHEN; Pei-dong ZHU; Yue-shan XIONG (Tongxin xuebao)
In online social networks,advertisements,rumors and malicious links are propagated by spammers arbitrarily.They not only disturb users’usualaccess,but also bring about network security threats and social panics.In an attempt to deal with the spam problems,an information diffusion model was proposed to capture the features of spam propagation.Propagation behaviors are quantitatively analyzed to detect spam messages with a decision tree-based method.The effectiveness of proposed detection model is evaluated with real data from the micro-bloggingnetwork of Sina.The experimental results show that proposed model can effectively detect spams in Sina micro-bloggingnetwork.